The effect of metallic Fe(ii) and nonmetallic S codoping on the photocatalytic performance of graphitic carbon nitride. Issue 14 (16th February 2018) - Dou, Hailong; Zheng, Shaohui; Zhang, Yongping
Abstract : The photoinduced electrons jump more easily to the conduction band of g-C3 N4 for the Fe impurity band locates above the valence band acting a bridge for electron transfer. Abstract : The metallic Fe(ii ) ion and nonmetallic S codoped g-C3 N4 photocatalyst was synthesized through the polymerization of melamine, ferrous chloride and trithiocyanuric acid (TCA) at elevated temperature. The performance of Fe(ii )–S codoped g-C3 N4 compounds in RhB photocatalytic degradation was found to increase 5 times. This significant enhancement in catalytic activity is probably related to the enhanced visible light adsorption and the mobility of photoinduced electron/hole pairs, attributable to bandgap narrowing and also lowering in the surface electrostatic potential compared to that of the pure g-C3 N4 nanosheets. XRD and XPS results indicate that the Fe species binds with N-atoms to form Fe–N bonds in the state of Fe(ii ) ions. Fe(ii ) doping increases the specific surface area, and enhances the photoinduced electron/hole pairs illustrated by PL, EIS spectra and transient photocurrent response measurements. The theoretical results show that divalent Fe(ii ) ions coordinating in the pore centre among three triazine units form discrete dopant bands and S dopants substituting the N in triazine skeletons excite much stronger delocalized HOMO and LUMO states, facilitating the migration of photogenerated charge carriers, thus enhancing the visible-light driven photocatalytic performance.